The importance of introducing different painting materials and techniques in the 5th-6th forms of secondary schools - Norkus , V. (Psichologija, 1972)
The training of creative abilities is the principal task of youth communist education. At the drawing lessons this problem has been solved mainly through the contents of instruction in conformity with the traditional rules of academic drawing. Up to now little attention was paid to the use of various painting materials and techniques in the process of training. The use of different painting materials and techniques at the drawing lessons effects pupils’ mental and physical qualities, broadens their outlook, develops their creative abilities, artistic taste and habits of drawing. Thus it is advisable to introduce water-colours, Indian ink, lead, stamping, drawing and other techniques at the drawing lessons in secondary school. After the acquaintance with various painting materials and techniques the pupils’ perception of folk and Professional art, of the synthesis of form and contents deepens.